Effect of roasting on utilization of sunflower oil seeds in nursery pig diets - G E Fitzner; T L Weeden; D F Li; D B Jones; Robert H Hines; Robert D Goodband; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred twelve weanling pigs were used to evaluate effects of diets containing 25% raw or low or high roasted sunflower seeds on performance. Pigs fed meal and pelleted diets containing sunflower seeds roasted to a roaster exit temperature of 264 of (low roast) were more efficient (F/G) than pigs fed raw sunflower seed diets in meal form. Pelleting raw, low roast, and high roast sunflower seed diets significantly improved F/G compared to raw sunflower seed and basal diets fed in meal form. These results indicate that meal diets containing 25% low roasted sunflower seeds or pelleted diets containing 25% raw or low roasted sunflower seeds can be fed to weaned pigs with no reduction in performance.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Nursery pigs; Sunflower seeds; Roasting; Pelleting